(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Through the field study, the research aims to evaluate the impact of strategic planning on the efficiency and effectiveness of small and medium enterprises in the Syrian Arab Republic. Assessing the impact of vision and mission as dimensions of strategic planning on the efficiency and effectiveness of small and medium enterprises, and thus presenting the results of the field study to benefit from them in development and change. . In this study, the researcher reached several results, the most important of which are: • Strategic planning has an effective role and great importance in influencing the efficiency and effectiveness of small and medium enterprises in Hama Governorate. • There are positive indicators that reinforce the importance of the vision and its impact on the efficiency and effectiveness of small and medium enterprises in Hama Governorate. • The results indicated that the vision of small and medium enterprises in Hama Governorate determines their current field of activity and future directions.